2015
DOI: 10.1155/2015/402926
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lipoid Pneumonia in a 9-Year-Old Child Revealed by Recurrent Chest Pain

Abstract: Lipoid pneumonia in children is a rare disorder due to accumulation of fatty oily material in the alveoli and usually associated with an underlying condition. In absence of obvious context, diagnosis remains difficult with nonspecific clinical and radiological features. We report the first case of voluntary chronic aspiration of olive oil responsible for exogenous lipoid pneumonia, in a previously healthy 9-year-old boy. Clinical presentation was atypical; LP was revealed by isolated chest pain. We discuss rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…One study reported oil ingestion in a child with a behavioural disorder who drank large amounts of oil when frustrated [39]. Regarding duration of oil use, majority of the studies reported on prolonged/repeated administration.…”
Section: Oil Use and Rationalementioning
confidence: 99%
See 3 more Smart Citations
“…One study reported oil ingestion in a child with a behavioural disorder who drank large amounts of oil when frustrated [39]. Regarding duration of oil use, majority of the studies reported on prolonged/repeated administration.…”
Section: Oil Use and Rationalementioning
confidence: 99%
“…These included Mycobacterium fortuitum [10,40,41], M. fortuitum/chelonei [42], Mycobacterium smegmatis [31] and Mycobacterium abscessus complex [24]. Other infections described in the selected studies included Branhamella catarrhalis [35]; Pseudomonas, Acinetobacter, Klebsiella [20]; respiratory viruses including Adenovirus, Human Metapneumovirus, Human Bocavirus, Human Rhinovirus, Parainfluenza, Respiratory Syncytial virus A and B, Coronavirus and various bacteria and fungi [24]; Chlamydia on serology [39]; and Enterococcus, Escherichia coli, Klebsiella, coagulase positive Staphylococcus and Clostridium from peritoneal exudate [29] (Appendix C).…”
Section: Microbiologymentioning
confidence: 99%
See 2 more Smart Citations